Voluntary activation and twitch potentiation of the elbow flexors across supinated, neutral, and pronated forearm orientations - Kohn, Sienna (Physiol Rep, 2018)
Elbow flexion force depends on forearm orientation with supinated and neutral being stronger than pronated. The purpose of this study was to assess the influence of forearm orientation on voluntary activation (VA), postactivation potentiation (PAP), and twitch properties. Eleven males (23 ± 3 years) performed isometric elbow flexion maximal voluntary contractions (MVC) in supinated, neutral, and pronated forearm orientations with supramaximal stimulation to the biceps brachii muscle belly before, during, and after the MVC. MVC and VA were higher in supinated (213.6 ± 49.6 N; 93.0 ± 5.2%) and neutral (243.6 ± 48.0 N; 96.1 ± 3.2%) compared with pronated (113.6 ± 21.3 N; 70.9 ± 20.4%) (P < 0.05), while PAP did not differ across the three orientations (71.6 ± 42.2%) (P > 0.05). In the rested state, pronated peak tension (PT) was less compared with supinated (42%). In the potentiated state, pronated PT was less than supinated (50%) and neutral (53%) (P < 0.05). Reduced strength in the pronated orientation is partially attributed to reduced drive; however, reductions in peak tension indicate that there also is a mechanical disadvantage when the forearm is placed into a pronated orientation, and this does not alter PAP.